Fluvial to tidal transition in proximal, mixed tide‐influenced and wave‐influenced deltaic deposits: Cretaceous lower Sego Sandstone, Utah, USA. Issue 6 (25th May 2016) - van Cappelle, Marijn; Stukins, Stephen; Hampson, Gary J.; Johnson, Howard D.
Abstract: Facies models for regressive, tide‐influenced deltaic systems are under‐represented in the literature compared with their fluvial‐dominated and wave‐dominated counterparts. Here, a facies model is presented of the mixed, tide‐influenced and wave‐influenced deltaic strata of the Sego Sandstone, which was deposited in the Western Interior Seaway of North America during the Late Cretaceous. Previous work on the Sego Sandstone has focused on the medial to distal parts of the outcrop belt where tides and waves interact. This study focuses on the proximal outcrop belt, in which fluvial and tidal processes interact. Five facies associations are recognized. Bioturbated mudstones (Facies Association 1) were deposited in an offshore environment and are gradationally overlain by hummocky cross‐stratified sandstones (Facies Association 2) deposited in a wave‐dominated lower shoreface environment. These facies associations are erosionally overlain by tide‐dominated cross‐bedded sandstones (Facies Association 4) interbedded with ripple cross‐laminated heterolithic sandstones (Facies Association 3) and channelized mudstones (Facies Association 5). Palaeocurrent directions derived from cross‐bedding indicate bidirectional currents which are flood‐dominated in the lower part of the studied interval and become increasingly ebb‐directed/fluvial‐directed upward. At the top of the succession, ebb‐dominated/fluvial‐dominated, high relief, narrow channel forms are present, which are interpreted as distributary channels. When distributary channels are abandoned they effectively become estuaries with landward sediment transport and fining trends. These estuaries have sandstones of Facies Association 4 at their mouth and fine landward through heterolithic sandstones of Facies Association 3 to channelized mudstones of Facies Association 5. Therefore, the complex distribution of relatively mud‐rich and sand‐rich deposits in the tide‐dominated part of the lower Sego Sandstone is attributed to the avulsion history of active fluvial distributaries, in response to a subtly expressed allogenic change in sediment supply and relative sea‐level controls and autocyclic delta lobe abandonment.